An economic evaluation of the costs of training a medical scribe to work in Emergency Medicine. Issue 12 (28th June 2016) - Walker, Katherine J; Dunlop, Will; Liew, Danny; Staples, Margaret P; Johnson, Matt; Ben-Meir, Michael; Rodda, Hamish Gordon; Turner, Ian; Phillips, David
Abstract : Objective: To undertake a cost analysis of training medical scribes in an ED. Methods: This was a pilot, observational, single-centre study at Cabrini ED, Melbourne, Australia, studying the costs of initiating a scribe programme from the perspective of the hospital and Australian Health sector. Recruitment and training occurred between August 2015 and February 2016 and comprised of a prework course (1 month), prework training sessions and clinical training shifts for scribe trainees (2–4 months, one shift per week) who were trained by emergency physicians. Costs of start-up, recruitment, administration, preclinical training, clinical training shifts and productivity changes for trainers were calculated. Results: 10 trainees were recruited to the prework course, 9 finished, 6 were offered clinical training after simulation assessment, 5 achieved competency. Scribes required clinical training ranging from 68 to 118 hours to become competent after initial classroom training. Medical students (2) required 7 shifts to become competent, premedical students (3) 8–16 shifts, while a trainee from an alternative background did not achieve competency. Based on a scribe salary of US$15.91/hour (including 25% on-costs) plus shift loadings, costs were: recruitment and start-up US$3111, education US$1257, administration US$866 and clinical shift costs US$1137 (overall cost US$6317 per competent scribe). Physicians who trained the clinical trainee scribes during shifts did not lose productivity. Conclusions: Training scribes outside the USA is feasible using an on-line training course and local physicians. It makes economic sense to hire individuals who can work over a long period of time to recoup training costs. Trial registration number: ACTRN12615000607572.